Analysis of Electronic Medical Record Information Systems in Outpatient Services Jalan Klinik Kusmahati 2 Sukoharjo - Licia, Rizka; Nanda Permatasari; Ummu Zahro, Salsabila; Khoirotunnisa, Aisyah; Ayu Kholifah, Fidiah (Journal Health Information Management Indonesian (JHIMI), 2022)
The form of advances in information technology in the health sector is Electronic Medical Records (RME). Basically electronic medical records use electronic methods for collecting, storing, processing and accessing patient medical records in health care facilities that have been stored in a multimedia database management system that collects various medical data sources. The purpose of this study was to analyze and implement a medical record information system for outpatient services at the Kusmahati 2 Sukoharjo Clinic. This research uses a descriptive research type that describes the data as a result of research. The subjects of this study were medical record officers, doctors, pharmacy installations and cashiers. While the object of this research is the implementation of the Electronic Medical Record System at the Kusmahati 2 Sukoharjo Clinic. The results of this study indicate that a web-based electronic medical record has been designed for the Kusmahati Dua Sukoharjo Clinic and is ready to be submitted to the owner of the Kusmahati Dua Sukoharjo Clinic for follow-up. Researchers suggest that electronic medical records be implemented in service activities at the Kusmahati Dua Sukoharjo Clinic so that they can be further evaluated and developed.